The Applications of Water‐in‐Salt Electrolytes in Electrochemical Energy Storage Devices. (27th October 2020) - Liang, Tingting; Hou, Ruilin; Dou, Qingyun; Zhang, Hongzhang; Yan, Xingbin
Abstract: Water‐in‐salt electrolytes (WISEs) have attracted widespread attention due to their non‐flammability, environmental friendliness, and wider electrochemical stability window than conventional dilute aqueous electrolytes. When applied in the electrochemical energy storage (EES) devices, WISEs can offer many advantages such as high‐level safety, manufacturing efficiency, as well as, superior electrochemical performances. Therefore, there is an urgent need for a timely and comprehensive summary of WISEs and their EES applications. In this review, the physicochemical and electrochemical properties of the WISEs are first introduced. Then, the research progresses of the WISEs using different metal salts and their analogues are summarized. Next, the current research progresses of WISEs applied in different EES devices (e.g., batteries and supercapacitors) as well as the insights into challenging and future perspectives are systematically discussed. Abstract : Water‐in‐salt electrolytes (WISEs) can offer many advantages such as high‐level safety, manufacturing efficiency, as well as superior electrochemical performance when applied in electrochemical energy storage (EES) devices. This is a timely and comprehensive summary of WISEs for EES applications; thus, this review provides constructive guidance to design more effective WIS‐based EES devices.